1986
DOI: 10.1088/0029-5515/26/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Alfvén waves and plasma production in the OMEGA and URAGAN-3 toroidal devices

Abstract: The paper describes a theoretical and experimental study of the structure of local Alfvén resonance (AR) and absorption of Alfvén waves (AWs) in an inhomogeneous toroidal plasma. An analysis is made of expressions for the RF field distribution in the AR region and for the power absorbed by the plasma, taking into account finite ion Larmor radius, inertia of electrons, the gyrotropy effect and Cherenkov absorption of waves by electrons. The dispersion characteristics of the AWs excited have been studied in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…In addition, with specifics of the Alfven wave excitation and absorption in the ω ω ci range of frequencies in a radially non-uniform plasma [9] and magnetic field taken into account, one may expect substantial non-uniformities in heating power deposition and intensity of FI generation both along the torus and over the minor azimuth.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, with specifics of the Alfven wave excitation and absorption in the ω ω ci range of frequencies in a radially non-uniform plasma [9] and magnetic field taken into account, one may expect substantial non-uniformities in heating power deposition and intensity of FI generation both along the torus and over the minor azimuth.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The plasma is produced and heated by RF fields in the frequency range ω ω ci (0) in the multi-mode Alfven resonance regime [9] with the working gas (hydrogen) continuously intake into the vacuum chamber. The RF power is injected into the plasma by the so-called frame-like antenna [9] embracing the plasma under the helical coils I and III within one field period (period 1 in Figure 1).…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When v T e < c A , a slow quasi-electrostatic Alfvén wave (SQEAW) is excited with mainly collision damping and propagates towards the plasma boundary. The detailed picture of resonant absorption was established by subsequent theoretical work carried out by different investigators (see, for example, [8]- [13]) and experimentally confirmed in tokamaks [14]- [17] and stellarator [1,18].…”
Section: Introductionmentioning
confidence: 99%
“…The working gas (hydrogen) is admitted into the chamber continuously at the pressure of 10 −6 − 10 −4 Torr. The plasma is produced and heated by RF fields (frame-type antenna) at the frequency 8.8 MHz (ω ω ci ) in the multi-mode Alfvén resonance regime [1]. The RF power P fed in the antenna attains 200 kW.…”
mentioning
confidence: 99%